Injury incidence and injury patterns by category, player position, and maturation in elite male handball elite players - Mónaco, M.; Gutiérrez Rincón, J. A.; Montoro Ronsano, B. J.; Whiteley, R.; Sanz-Lopez, F.; Rodas, G. (Biology of Sport, 2019)
The aim of this cohort study is to estimate the influence of position, category, and maturity status on the incidence and pattern of injury in handball players, across two seasons. Injury registration from 164 players per season (12-27 years) was conducted, and players were categorized into youth (133) and adults (31), and per position: 27 goalkeepers, 67 backs, 70 wings and pivots. Maturity status in youth players was also measured by testicular volume on clinical examination (32 immature, 101 mature). 190 injuries occurred during 34 221 hours of exposure. Injury incidence in youth was 6.0 per 1000 total hours [CI 95%, 4.8-7.2] (14.9 match [9.7-20.1] and 3.7 training hours [2.7-4.6]; n= 142 injuries), and in adults 6.5 per 1000 total hours [4.4-8.6] (22.2 match [8.8- 35.6] and 3.0 training hours [1.3-4.6]; n=48 injuries). There were significant differences in knee (P=0.01) and cartilage injury (P=0.05) according to playing position. There were significant differences according to age category in ankle (P=0.03), head (P=0.01), thigh (P=0.05) and muscular injury (P= 0.02), and apophysitis (P=0.04) for biological maturity state. Adult handball players had more ankle and muscle injuries than youths. Backs and centre backs (2nd line) had more knee and cartilage problems. A higher incidence of apophysitis was found in immature youth players.